Skin-friendly antibacterial foaming material and application thereof in footwear products

The modified polyamide produced by polymerizing polyetheramine, dimethyl furan-2,5-dimethyl sulfonic acid, 3,5-diaminobenzenesulfonic acid, and dimethyl malonic acid is blended with functionalized polysiloxane, modified silica, and chitosan quaternary ammonium salts to foam, and the skin-friendly and antibacterial foaming materials are solved, which solves the problems of bacterial growth, wear, tear and other problems in long-term use of existing footwear materials, and provides a safe use experience in high-temperature and high-pressure environments, achieving good antibacterial, flame retardant and self-healing properties.

CN119823565AActive Publication Date: 2025-04-15ALPHA (GUANGDONG) HIGH-TECH MATERIALS CO LTD

Patent Information

Application Number
CN202510040347.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Existing footwear materials are prone to bacterial growth, wear, tear and other problems during long-term use, and are prone to burn in high-temperature and high-pressure environments, which poses safety hazards.

Method used

The skin-friendly and antibacterial foaming material is made of modified polyamide prepared by polymerization of polyetheramine, dimethyl furan-2,5-diaminobenzenesulfonic acid, dimethyl malonic acid and mixed foaming with functionalized polysiloxane, modified silica, and chitosan quaternary ammonium salts.

Benefits of technology

The material has good antibacterial, flame retardant and self-healing properties, which can effectively prevent bacteria from growing, reduce wear and tear, and provide a safe user experience in high temperature and high pressure environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a skin-friendly antibacterial foaming material and application thereof in footwear products, and relates to the technical field of high polymer materials. When the skin-friendly antibacterial foaming material is prepared, firstly, tetramethyl tetravinyl cyclotetrasiloxane and a flame retardant react to obtain flame-retardant cyclosiloxane, 1, 3-bis (aminopropyl-1, 1, 3, 3-tetramethyl disiloxane and maleic anhydride react to obtain an end-capping reagent, the flame-retardant cyclosiloxane and octamethyl cyclotetrasiloxane are subjected to ring opening polymerization, and the skin-friendly antibacterial foaming material is obtained. Carrying out end-capping by an end-capping reagent to obtain functionalized polysiloxane, loading a foaming agent on hollow silicon dioxide, and grafting chitosan quaternary ammonium salt; and finally, polymerizing polyether amine, furan-2, 5-dimethyl dicarboxylate, 3, 5-diaminobenzene sulfonic acid and dimethyl malonate to prepare modified polyamide, and blending and foaming the modified polyamide, the functionalized polysiloxane, the modified silicon dioxide and chitosan quaternary ammonium salt to prepare the skin-friendly antibacterial foaming material. The prepared skin-friendly antibacterial foaming material has excellent flame retardance, antibacterial performance and self-repairing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a skin-friendly antibacterial foaming material and application thereof in footwear products. Background Art

[0002] As people's requirements for quality of life continue to improve, the comfort, skin-friendliness and durability of footwear products have become the focus of consumers. As one of the most important engineering plastics, polyamide foam materials have excellent mechanical and elastic properties and have very broad prospects in the footwear industry.

[0003] Traditional footwear materials are often exposed to problems such as bacterial growth and varying degrees of wear and tear during long-term use. These problems not only affect the service life of the shoes, but may also pose a potential threat to the health of the wearer. In addition, in some usage environments, such as outdoor campfires and working environments under high temperature and high voltage, spark splashes can easily cause footwear to burn, posing a safety hazard. Therefore, the development of a new foaming material that combines antibacterial, flame retardant and self-healing properties has become an important research direction in the field of footwear products. Summary of the invention

[0004] The object of the present invention is to provide a skin-friendly antibacterial foaming material and application thereof in footwear products, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A skin-friendly antibacterial foaming material is prepared by blending and foaming modified polyamide prepared by polymerization of polyetheramine, furan-2,5-dimethyl dicarboxylate, 3,5-diaminobenzenesulfonic acid and dimethyl malonate, and functionalized polysiloxane, modified silicon dioxide and chitosan quaternary ammonium salt.

[0007] As an optimization, the functionalized polysiloxane is first obtained by reacting tetramethyltetravinylcyclotetrasiloxane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to obtain flame-retardant cyclosiloxane, ring-opening polymerization of the flame-retardant cyclosiloxane and octamethylcyclotetrasiloxane, and then capping with a capping agent.

[0008] As an optimization, the capping agent is prepared by reacting 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and maleic anhydride.

[0009] As an optimization, the modified silica is prepared by loading a foaming agent on hollow silica, then modifying with 3-aminopropyltriethoxysilane to obtain amino silica, reacting the amino silica with succinic anhydride to obtain carboxylated silica, and then grafting the carboxylated silica with chitosan quaternary ammonium salt.

[0010] A method for preparing a skin-friendly antibacterial foaming material comprises the following preparation steps:

[0011] (1) tetramethyltetravinylcyclotetrasiloxane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and chloroform are mixed in a mass ratio of 1:(0.5-0.7):(20-30), heated to 65-70° C. for reflux reaction for 5-10 min, azobisisobutyronitrile in an amount of 0.01-0.02 times the mass of tetramethyltetravinylcyclotetrasiloxane is added, the reaction is continued for 6-7 h, chloroform is removed by vacuum rotary evaporation, and the mixture is dried at 60° C. for 6-7 h to obtain a flame retardant cyclosiloxane;

[0012] (2) octamethylcyclotetrasiloxane and flame retardant cyclosiloxane are mixed in a mass ratio of 1:(0.3-0.5), heated to 80° C. under nitrogen protection, mixed for 1 hour, added with a 25wt% tetramethylammonium hydroxide aqueous solution of 0.02%-0.03% by weight of octamethylcyclotetrasiloxane, and then added with a capping agent of 0.3%-0.4% by weight of octamethylcyclotetrasiloxane, and continued to heat to 110-120° C., reacted for 2-3 hours, and continued to heat to 150° C., reduced pressure to 2-2.5 KPa, and reacted for 3-4 hours to obtain a functionalized polysiloxane;

[0013] (3) under nitrogen protection, polyetheramine and 3,5-diaminobenzenesulfonic acid are mixed at a mass ratio of 1:(0.2-0.3) to obtain a diamine mixture, dimethyl malonate and furan-2,5-dicarboxylate are mixed at a mass ratio of 1:(0.2-0.3) to obtain a diacid methyl ester mixture, and the diamine mixture and the diacid methyl ester mixture are stirred uniformly at a molar ratio of 1:1, wherein the molar ratio refers to the molar ratio of the amino group in the diamine mixture to the methyl ester group in the diacid methyl ester mixture, the stirring speed is 200-300 r / min, the reaction is carried out at 120° C. for 30-40 min, the temperature is raised to 230-240° C., and the reaction is carried out at 300 Pa for 2-2.5 h to obtain a modified polyamide;

[0014] (4) Mixing supported silica and toluene in a mass ratio of 1:(50-60), uniformly dispersing by ultrasonication at 40 Hz, adding 3-aminopropyltriethoxysilane in an amount of 10-12 times the mass of supported silica, heating to 100-110° C., reflux reaction for 22-24 h, cooling to room temperature, filtering and washing with pure water for 3-4 times, and drying at 60° C. for 6-8 h to obtain amino silica; mixing amino silica, succinic anhydride, 4-dimethylaminopyridine and dichloromethane in a mass ratio of 1:(3-4):(0.7-0.9):(100-150), stirring at room temperature for 10-12 h, filtering and washing with ethanol for 3-4 times, and drying at 60° C. for 6-8 h to obtain carboxylated silica;

[0015] (5) Carboxylated silica, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and pure water are mixed at a mass ratio of 1:1:(150-160) for 30 minutes, N-hydroxysuccinimide is added in an amount equal to the mass of the carboxylated silica, and stirring is continued for 30 minutes to obtain a silica dispersion, chitosan quaternary ammonium salt and pure water in an amount equal to the mass of the carboxylated silica are added in a mass ratio of 1:(150-160) at 60° C. for 5-6 hours, and then added to the silica dispersion, stirred at 60° C. for 10-12 hours, cooled to room temperature, stirred for 10-12 hours, filtered, and dried at 60° C. for 6-8 hours to obtain modified silica;

[0016] (6) Grinding the modified polyamide into modified polyamide powder using a ball mill, wherein the diameter of the grinding balls in the ball mill is 6 mm, the grinding time is 10 h, the ball-to-material mass ratio is 1:(1.1-1.2), and the rotation speed of the ball mill is 500-600 r / min; adding the modified polyamide powder into a torque rheometer at 60 r / min and 190 ° C and stirring for 1 min, then adding functionalized polysiloxane, modified silica, and chitosan quaternary ammonium salt and kneading for 6 min, discharging the material and placing it in a foaming mold, placing the foaming mold in a high-temperature foaming machine for foaming, and keeping it at 180 ° C and 11 MPa for 7 min before demolding to obtain a skin-friendly and antibacterial foaming material.

[0017] As an optimization, the preparation method of the end-capping agent in step (2) is as follows: under nitrogen protection, 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and maleic anhydride are weighed in a mass ratio of 1:(2.1-2.2), 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and toluene are mixed in a mass ratio of 1:(30-40) to obtain solution A, maleic anhydride and toluene are mixed in a mass ratio of 1:(50-60) to obtain solution B, solution B is added dropwise to solution A at a dropping rate of 6 mL / min, reacted at room temperature for 1-1.5 h, then heated to 80° C., acetic anhydride with a mass of 0.7-0.9 times that of maleic anhydride and pyridine with a mass of 0.5-0.7 times that of maleic anhydride are added, the reaction is continued for 3-4 h, and toluene is removed by reduced pressure rotary evaporation to obtain the end-capping agent.

[0018] As an optimization, the preparation method of the supported silica in step (4) is as follows: polystyrene microspheres, hexadecyltrimethylammonium bromide, 25wt% ammonia water, and anhydrous ethanol are mixed in a mass ratio of 1: (0.3-0.5): (10-12): (100-150), and after ultrasonication at 40 Hz for 50-60 min, 5-6 times the mass of tetraethyl orthosilicate of the polystyrene microspheres is added, and the reaction is stirred for 8-10 h at room temperature, filtered and dried at 60° C. for 4-6 h, and then calcined at 500° C. for 6 h to obtain hollow silica; the hollow silica is immersed in a foaming agent solution, stirred for 30 min, and ultrasonicated at 40 Hz for 10-20 min, allowed to stand for 24 h, filtered, and washed with methanol for 3-4 times, and dried at 60° C. for 6-8 h to obtain supported silica.

[0019] As an optimization, the foaming agent solution is prepared by mixing azodicarbonamide and dimethyl sulfoxide in a mass ratio of 1:(15-17); and the particle size of the polystyrene microspheres is 3 μm.

[0020] As an optimization, the amounts of the modified polyamide powder, functionalized polysiloxane, modified silica, and chitosan quaternary ammonium salt in step (6) are: by mass, 100 parts of modified polyamide powder, 1-2 parts of functionalized polysiloxane, 3-5 parts of modified silica, and 3-5 parts of chitosan quaternary ammonium salt.

[0021] As an optimization, the chitosan quaternary ammonium salt in step (5) and step (6) is hydroxypropyltrimethylammonium chloride chitosan with a degree of substitution of 98%.

[0022] As an optimization, the polyetheramine in step (3) is polypropylene glycol bis(2-aminopropyl ether) with a molecular weight of 2000.

[0023] The present invention also provides an application of the skin-friendly antibacterial foaming material prepared according to the preparation method of the skin-friendly antibacterial foaming material in footwear products.

[0024] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0025] When preparing the skin-friendly antibacterial material, the present invention comprises the following steps: firstly, tetramethyltetravinylcyclotetrasiloxane and a flame retardant are reacted to obtain a flame-retardant cyclosiloxane; 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and maleic anhydride are reacted to obtain a capping agent; the flame-retardant cyclosiloxane and octamethylcyclotetrasiloxane are ring-opening polymerized; a functionalized polysiloxane is obtained by capping with the capping agent; and then a foaming agent is loaded on hollow silica and grafted onto chitosan quaternary ammonium salt; and finally, a modified polyamide obtained by polymerizing polyetheramine, furan-2,5-dimethyl dicarboxylate, 3,5-diaminobenzenesulfonic acid and dimethyl malonate, and the functionalized polysiloxane, the modified silica and the chitosan quaternary ammonium salt are blended and foamed to obtain the skin-friendly antibacterial foaming material.

[0026] Firstly, the carbon-carbon double bond on tetramethyltetravinylcyclotetrasiloxane reacts with the phosphorus-hydrogen of the flame retardant 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to generate a flame retardant cyclosiloxane, the amino groups at both ends of 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and maleic anhydride are amidated and dehydrated to generate maleimide-terminated siloxane, the flame retardant cyclosiloxane, octamethylcyclotetrasiloxane and maleimide-terminated siloxane are reacted to generate maleimide-terminated polysiloxane, the side chain of the polysiloxane contains a flame retardant functional monomer, which can give the material excellent flame retardant properties;

[0027] Then, the hollow silica is loaded with a foaming agent, and the surface of the silica is carboxylated by modification with a silane coupling agent and succinic anhydride, and then chitosan quaternary ammonium salt is grafted to give the material good antibacterial properties. Since the surface of the silica carries a positive charge, it can also attract the positive and negative charges with the modified polyamide having a sulfonic acid structure in the main chain, thereby enhancing the compatibility of the silica and the polyamide, and enhancing the dispersibility of the silica in the polyamide. Since the pure foaming agent itself has a large particle size and poor compatibility with polyamide, it will lead to excessive local gas emission and lack of nucleation points in the polymer matrix. The silica-loaded foaming agent can not only enhance the wear resistance of the material, but also improve the dispersion of the foaming agent in the polyamide. The hollow silica microspheres can also serve as nucleation points for bubbles to improve the uniformity of foaming.

[0028] Finally, the modified polyamide obtained by polymerization of polyetheramine, furan-2,5-dicarboxylic acid dimethyl ester, 3,5-diaminobenzenesulfonic acid, and dimethyl malonate was blended and foamed with functionalized polysiloxane, modified silica, and chitosan quaternary ammonium salt to obtain a skin-friendly antibacterial foaming material. The furan group in the modified polyamide main chain can not only form a dynamic reversible covalent bond with the maleimide groups at both ends of the functionalized polysiloxane, giving the material self-healing properties, but also introduce a cross-linking structure, change the linear molecular chain structure of the polyamide, increase the melt strength, and improve the shrinkage phenomenon during the foaming process; chitosan quaternary ammonium salt has good biocompatibility and good affinity with human skin, which can give the material good skin-friendly properties. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] The chitosan quaternary ammonium salt used in all the following examples and comparative examples is hydroxypropyltrimethylammonium chloride chitosan with a substitution degree of 98%; the particle size of the polystyrene microspheres is 3 μm; and the polyetheramine is polypropylene glycol bis(2-aminopropyl ether) with a molecular weight of 2000.

[0031] Example 1

[0032] A skin-friendly antibacterial foaming material, the preparation method is as follows:

[0033] (1) tetramethyltetravinylcyclotetrasiloxane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and chloroform are mixed in a mass ratio of 1:0.5:20, heated to 70° C. and refluxed for 10 min, azobisisobutyronitrile in an amount of 0.01 times the mass of tetramethyltetravinylcyclotetrasiloxane is added, reacted for 7 h, chloroform is removed by vacuum rotary evaporation, and dried at 60° C. for 7 h to obtain a flame retardant cyclosiloxane;

[0034] (2) Under nitrogen protection, 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and maleic anhydride were weighed in a mass ratio of 1:2.1, 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and toluene were mixed in a mass ratio of 1:30 to obtain solution A, maleic anhydride and toluene were mixed in a mass ratio of 1:50 to obtain solution B, solution B was added dropwise to solution A at a dropping speed of 6 mL / min, reacted at room temperature for 1.5 h, then heated to 80° C., acetic anhydride and maleic acid in an amount 0.7 times the mass of maleic anhydride were added, and the mixture was stirred for 1.5 h. 0.5 times the mass of pyridine of anhydride, continue to react for 4 hours, remove toluene by vacuum rotary evaporation to obtain a capping agent; octamethylcyclotetrasiloxane and flame retardant cyclosiloxane are mixed in a mass ratio of 1:0.3, heated to 80°C under nitrogen protection, mixed for 1 hour, 0.02% of the mass of octamethylcyclotetrasiloxane by 25wt% tetramethylammonium hydroxide aqueous solution, and then 0.3% of the mass of octamethylcyclotetrasiloxane by the capping agent, continue to heat to 120°C, react for 3 hours, continue to heat to 150°C, reduce the pressure to 2.5KPa, react for 4 hours, and obtain functionalized polysiloxane;

[0035] (3) under nitrogen protection, polyetheramine and 3,5-diaminobenzenesulfonic acid were mixed at a mass ratio of 1:0.2 to obtain a diamine mixture, dimethyl malonate and furan-2,5-dicarboxylic acid dimethyl ester were mixed at a mass ratio of 1:0.2 to obtain a diacid methyl ester mixture, and the diamine mixture and the diacid methyl ester mixture were stirred uniformly at a molar ratio of 1:1, wherein the molar ratio refers to the molar ratio of the amino group in the diamine mixture to the methyl ester group in the diacid methyl ester mixture, the stirring speed was 300 r / min, the reaction was carried out at 120° C. for 40 min, the temperature was raised to 240° C., and the reaction was carried out at 300 Pa for 2.5 h to obtain a modified polyamide;

[0036] (4) Azodicarbonamide and dimethyl sulfoxide are mixed in a mass ratio of 1:15 to obtain a foaming agent solution; polystyrene microspheres, hexadecyltrimethylammonium bromide, 25wt% ammonia water, and anhydrous ethanol are mixed in a mass ratio of 1:0.3:10:100, and after ultrasonication at 40 Hz for 60 minutes, 5 times the mass of tetraethyl orthosilicate of the polystyrene microspheres is added, and the mixture is stirred for 10 hours at room temperature, filtered, dried at 60°C for 6 hours, and calcined at 500°C for 6 hours to obtain hollow silica; the hollow silica is immersed in the foaming agent solution, stirred for 30 minutes, ultrasonicated at 40 Hz for 20 minutes, allowed to stand for 24 hours, filtered, and washed with methanol 4 times , dried at 60°C for 8h to obtain supported silica; mixed supported silica and toluene in a mass ratio of 1:50, uniformly dispersed by ultrasonication at 40Hz, added 3-aminopropyltriethoxysilane 10 times the mass of supported silica, heated to 110°C, refluxed for 24h, cooled to room temperature, filtered, washed with pure water 4 times, and dried at 60°C for 8h to obtain amino silica; mixed amino silica, succinic anhydride, 4-dimethylaminopyridine and dichloromethane in a mass ratio of 1:3:0.7:100, stirred at room temperature for 12h, filtered, washed with ethanol 4 times, and dried at 60°C for 8h to obtain carboxylated silica;

[0037] (5) Carboxylated silica, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and pure water were mixed at a mass ratio of 1:1:150 for 30 minutes, N-hydroxysuccinimide was added in an amount equal to the mass of the carboxylated silica and the mixture was stirred for 30 minutes to obtain a silica dispersion, chitosan quaternary ammonium salt and pure water in an amount equal to the mass of the carboxylated silica were stirred at 60° C. for 6 hours at a mass ratio of 1:150, and then added to the silica dispersion, stirred at 60° C. for 12 hours, cooled to room temperature, stirred for 12 hours, filtered, and dried at 60° C. for 8 hours to obtain modified silica;

[0038] (6) Use a ball mill to grind the modified polyamide into modified polyamide powder, wherein the diameter of the grinding balls in the ball mill is 6 mm, the grinding time is 10 h, the ball-to-material mass ratio is 1:1.1, and the speed of the ball mill is 600 r / min; weigh 100 parts of modified polyamide powder, 1 part of functionalized polysiloxane, 3 parts of modified silica, and 3 parts of chitosan quaternary ammonium salt by mass; add the modified polyamide powder to a torque rheometer at 60 r / min and 190°C and stir for 1 min, then add functionalized polysiloxane, modified silica, and chitosan quaternary ammonium salt and knead for 6 min, then discharge the material and put it into a foaming mold, place the foaming mold in a high-temperature foaming machine for foaming, and demold after keeping warm at 180°C and 11 MPa for 7 min to obtain a skin-friendly and antibacterial foaming material.

[0039] Example 2

[0040] A skin-friendly antibacterial foaming material, the preparation method is as follows:

[0041] (1) Tetramethyltetravinylcyclotetrasiloxane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and chloroform are mixed in a mass ratio of 1:0.6:25, heated to 67° C. and refluxed for 8 min, azobisisobutyronitrile in an amount of 0.015 times the mass of tetramethyltetravinylcyclotetrasiloxane is added, reacted for 6.5 h, chloroform is removed by vacuum rotary evaporation, and dried at 60° C. for 6.5 h to obtain a flame retardant cyclosiloxane;

[0042] (2) Under nitrogen protection, 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and maleic anhydride were weighed in a mass ratio of 1:2.15, 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and toluene were mixed in a mass ratio of 1:35 to obtain solution A, maleic anhydride and toluene were mixed in a mass ratio of 1:55 to obtain solution B, solution B was added dropwise to solution A at a dropping rate of 6 mL / min, reacted at room temperature for 1.3 h, then heated to 80° C., acetic anhydride (0.8 times the mass of maleic anhydride) and maleic anhydride (0.05 times the mass of maleic anhydride) were added, and the reaction mixture was stirred for 1 h. .6 times of pyridine, continue to react for 3.5 hours, remove toluene by vacuum rotary evaporation to obtain a capping agent; octamethylcyclotetrasiloxane and flame retardant cyclosiloxane are mixed in a mass ratio of 1:0.4, heated to 80°C under nitrogen protection, mixed for 1 hour, 0.025% of the mass of octamethylcyclotetrasiloxane in a 25wt% tetramethylammonium hydroxide aqueous solution, and then 0.35% of the mass of octamethylcyclotetrasiloxane The capping agent is added and continued to heat to 115°C, react for 2.5 hours, continue to heat to 150°C, reduce the pressure to 2.3KPa, react for 3.5 hours, and obtain a functionalized polysiloxane;

[0043] (3) under nitrogen protection, polyetheramine and 3,5-diaminobenzenesulfonic acid were mixed at a mass ratio of 1:0.25 to obtain a diamine mixture, dimethyl malonate and furan-2,5-dicarboxylic acid dimethyl ester were mixed at a mass ratio of 1:0.25 to obtain a diacid methyl ester mixture, and the diamine mixture and the diacid methyl ester mixture were stirred uniformly at a molar ratio of 1:1, wherein the molar ratio refers to the molar ratio of the amino group in the diamine mixture to the methyl ester group in the diacid methyl ester mixture, the stirring speed was 250 r / min, the reaction was carried out at 120° C. for 35 min, the temperature was raised to 235° C., and the reaction was carried out at 300 Pa for 2.3 h to obtain a modified polyamide;

[0044] (4) Azodicarbonamide and dimethyl sulfoxide are mixed in a mass ratio of 1:16 to obtain a foaming agent solution; polystyrene microspheres, hexadecyltrimethylammonium bromide, 25wt% ammonia water, and anhydrous ethanol are mixed in a mass ratio of 1:0.4:11:125, and after ultrasonication at 40 Hz for 55 min, 5.5 times the mass of tetraethyl orthosilicate of the polystyrene microspheres is added, and the mixture is stirred for 9 h at room temperature, filtered, dried at 60°C for 5 h, and calcined at 500°C for 6 h to obtain hollow silica; the hollow silica is immersed in the foaming agent solution, stirred for 30 min, ultrasonicated at 40 Hz for 15 min, allowed to stand for 24 h, filtered, and washed with methanol 3 times , dried at 60°C for 7h to obtain supported silica; mixed supported silica and toluene in a mass ratio of 1:55, uniformly dispersed by ultrasonication at 40Hz, added 3-aminopropyltriethoxysilane 11 times the mass of supported silica, heated to 105°C, refluxed for 23h, cooled to room temperature and filtered, washed 3 times with pure water, and dried at 60°C for 7h to obtain amino silica; mixed amino silica, succinic anhydride, 4-dimethylaminopyridine and dichloromethane in a mass ratio of 1:3.5:0.8:125, stirred at room temperature for 11h, filtered, washed 4 times with ethanol, and dried at 60°C for 7h to obtain carboxylated silica;

[0045] (5) Carboxylated silica, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and pure water were mixed at a mass ratio of 1:1:155 for 30 minutes, N-hydroxysuccinimide was added in an amount equal to the mass of the carboxylated silica, and the mixture was stirred for 30 minutes to obtain a silica dispersion, chitosan quaternary ammonium salt and pure water in an amount equal to the mass of the carboxylated silica were stirred at 60° C. for 5.5 hours, and then added to the silica dispersion, stirred at 60° C. for 11 hours, cooled to room temperature, stirred for 11 hours, filtered, and dried at 60° C. for 7 hours to obtain modified silica;

[0046] (6) Use a ball mill to grind the modified polyamide into modified polyamide powder, wherein the diameter of the grinding balls in the ball mill is 6 mm, the grinding time is 10 h, the ball-to-material mass ratio is 1:1.15, and the speed of the ball mill is 550 r / min; weigh 100 parts of modified polyamide powder, 1.5 parts of functionalized polysiloxane, 4 parts of modified silica, and 4 parts of chitosan quaternary ammonium salt by mass; add the modified polyamide powder to a torque rheometer at 60 r / min and 190°C and stir for 1 min, then add functionalized polysiloxane, modified silica, and chitosan quaternary ammonium salt and knead for 6 min, then discharge the material and put it into a foaming mold, place the foaming mold in a high-temperature foaming machine for foaming, and demold after keeping warm at 180°C and 11 MPa for 7 min to obtain a skin-friendly and antibacterial foaming material.

[0047] Example 3

[0048] A skin-friendly antibacterial foaming material, the preparation method is as follows:

[0049] (1) tetramethyltetravinylcyclotetrasiloxane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and chloroform are mixed in a mass ratio of 1:0.7:30, heated to 65° C. and refluxed for 5 min, azobisisobutyronitrile in an amount of 0.02 times the mass of tetramethyltetravinylcyclotetrasiloxane is added, reacted for 6 h, chloroform is removed by vacuum rotary evaporation, and dried at 60° C. for 6 h to obtain a flame retardant cyclosiloxane;

[0050] (2) Under nitrogen protection, 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and maleic anhydride were weighed in a mass ratio of 1:2.2, 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and toluene were mixed in a mass ratio of 1:40 to obtain solution A, maleic anhydride and toluene were mixed in a mass ratio of 1:60 to obtain solution B, solution B was added dropwise to solution A at a dropping speed of 6 mL / min, reacted at room temperature for 1 h, then heated to 80°C, acetic anhydride and maleic acid in an amount 0.9 times the mass of maleic anhydride were added, and the mixture was stirred for 1 h. 0.7 times the mass of pyridine of anhydride, continue to react for 3 hours, remove toluene by vacuum rotary evaporation to obtain a capping agent; octamethylcyclotetrasiloxane and flame retardant cyclosiloxane are mixed in a mass ratio of 1:0.5, heated to 80°C under nitrogen protection, mixed for 1 hour, 0.03% of the mass of octamethylcyclotetrasiloxane by 25wt% tetramethylammonium hydroxide aqueous solution, and then 0.4% of the mass of octamethylcyclotetrasiloxane by the capping agent, continue to heat to 110°C, react for 2 hours, continue to heat to 150°C, reduce the pressure to 2KPa, react for 3 hours, and obtain functionalized polysiloxane;

[0051] (3) under nitrogen protection, polyetheramine and 3,5-diaminobenzenesulfonic acid were mixed at a mass ratio of 1:0.3 to obtain a diamine mixture, dimethyl malonate and furan-2,5-dicarboxylic acid dimethyl ester were mixed at a mass ratio of 1:0.3 to obtain a diacid methyl ester mixture, and the diamine mixture and the diacid methyl ester mixture were stirred uniformly at a molar ratio of 1:1, wherein the molar ratio refers to the molar ratio of the amino group in the diamine mixture to the methyl ester group in the diacid methyl ester mixture, the stirring speed was 200 r / min, the reaction was carried out at 120° C. for 30 min, the temperature was raised to 230° C., and the reaction was carried out at 300 Pa for 2 h to obtain a modified polyamide;

[0052] (4) Azodicarbonamide and dimethyl sulfoxide are mixed in a mass ratio of 1:17 to obtain a foaming agent solution; polystyrene microspheres, hexadecyltrimethylammonium bromide, 25wt% ammonia water, and anhydrous ethanol are mixed in a mass ratio of 1:0.5:12:150, and after ultrasonication at 40 Hz for 50 min, ethyl orthosilicate of 6 times the mass of the polystyrene microspheres is added, and the mixture is stirred for 8 h at room temperature, filtered, dried at 60°C for 4 h, and calcined at 500°C for 6 h to obtain hollow silica; the hollow silica is immersed in the foaming agent solution, stirred for 30 min, ultrasonicated at 40 Hz for 10 min, allowed to stand for 24 h, filtered, and washed with methanol 3 times , dried at 60°C for 6h to obtain supported silica; mixed supported silica and toluene in a mass ratio of 1:60, uniformly dispersed by ultrasonication at 40Hz, added 3-aminopropyltriethoxysilane 12 times the mass of supported silica, heated to 100°C, refluxed for 22h, filtered after cooling to room temperature and washed with pure water 3 times, dried at 60°C for 6h to obtain amino silica; mixed amino silica, succinic anhydride, 4-dimethylaminopyridine and dichloromethane in a mass ratio of 1:4:0.9:150, stirred at room temperature for 10h, filtered and washed with ethanol 3 times, dried at 60°C for 6h to obtain carboxylated silica;

[0053] (5) Carboxylated silica, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and pure water were mixed at a mass ratio of 1:1:160 for 30 minutes, N-hydroxysuccinimide was added in an amount equal to the mass of the carboxylated silica, and the mixture was stirred for 30 minutes to obtain a silica dispersion, chitosan quaternary ammonium salt and pure water in an amount equal to the mass of the carboxylated silica were stirred at 60° C. for 5 hours, and then added to the silica dispersion, stirred at 60° C. for 10 hours, cooled to room temperature, stirred for 10 hours, filtered, and dried at 60° C. for 6 hours to obtain modified silica;

[0054] (6) Use a ball mill to grind the modified polyamide into modified polyamide powder, wherein the diameter of the grinding balls in the ball mill is 6 mm, the grinding time is 10 h, the ball-to-material mass ratio is 1:1.2, and the speed of the ball mill is 500 r / min; weigh 100 parts of modified polyamide powder, 2 parts of functionalized polysiloxane, 5 parts of modified silica, and 5 parts of chitosan quaternary ammonium salt by mass; add the modified polyamide powder to a torque rheometer at 60 r / min and 190°C and stir for 1 min, then add functionalized polysiloxane, modified silica, and chitosan quaternary ammonium salt and knead for 6 min, then discharge the material and put it into a foaming mold, place the foaming mold in a high-temperature foaming machine for foaming, and demold after keeping warm at 180°C and 11 MPa for 7 min to obtain a skin-friendly and antibacterial foaming material.

[0055] Comparative Example 1

[0056] The difference between Comparative Example 1 and Example 2 is that step (1) is not included, and step (3) is modified as follows: under nitrogen protection, 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and maleic anhydride are weighed in a mass ratio of 1:2.15, 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and toluene are mixed in a mass ratio of 1:35 to obtain solution A, maleic anhydride and toluene are mixed in a mass ratio of 1:55 to obtain solution B, solution B is added dropwise to solution A at a dropping speed of 6 mL / min, the reaction is carried out at room temperature for 1.3 h, and then the temperature is raised to 80°C. Add acetic anhydride in an amount of 0.8 times the mass of maleic anhydride and pyridine in an amount of 0.6 times the mass of maleic anhydride, continue the reaction for 3.5 hours, remove toluene by rotary evaporation under reduced pressure to obtain a capping agent; under nitrogen protection, heat octamethylcyclotetrasiloxane to 80°C, stir for 1 hour, add 25wt% tetramethylammonium hydroxide aqueous solution in an amount of 0.025% by mass of octamethylcyclotetrasiloxane, then add 0.35% by mass of the capping agent of octamethylcyclotetrasiloxane, continue to heat to 115°C, react for 2.5 hours, continue to heat to 150°C, reduce the pressure to 2.3 KPa, react for 3.5 hours, and obtain a functionalized polysiloxane.

[0057] Comparative Example 2

[0058] The difference between Comparative Example 2 and Example 2 is that step (5) is not included, and step (4) is modified as follows: azodicarbonamide and dimethyl sulfoxide are mixed in a mass ratio of 1:16 to obtain a foaming agent solution; polystyrene microspheres, hexadecyltrimethylammonium bromide, 25wt% ammonia water, and anhydrous ethanol are mixed in a mass ratio of 1:0.4:11:125, and after ultrasonication at 40 Hz for 55 min, 5.5 times the mass of tetraethyl orthosilicate of the polystyrene microspheres is added, and the reaction is stirred for 9 h at room temperature, filtered and dried at 60°C for 5 h, and then calcined at 500°C for 6 h to obtain hollow silica; the hollow silica is immersed in the foaming agent solution, stirred for 30 min, and ultrasonicated at 40 Hz for 15 min, allowed to stand for 24 h, filtered, washed with methanol 3 times, and dried at 60°C for 7 h to obtain modified silica.

[0059] Comparative Example 3

[0060] The difference between Comparative Example 3 and Example 2 is that step (2) is modified as follows: octamethylcyclotetrasiloxane and flame retardant cyclosiloxane are mixed in a mass ratio of 1:0.4, heated to 80°C under nitrogen protection, mixed for 1 hour, 0.025% of the mass of octamethylcyclotetrasiloxane in a 25wt% tetramethylammonium hydroxide aqueous solution is added, and then 0.35% of the mass of octamethylcyclotetrasiloxane in 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane is added, and the temperature is continued to be raised to 115°C, reacted for 2.5 hours, and then continued to be raised to 150°C, the pressure is reduced to 2.3 KPa, and the reaction is carried out for 3.5 hours to obtain a functionalized polysiloxane.

[0061] Test Example 1

[0062] Flame retardant performance test

[0063] Test method: The limiting oxygen index of the foamed materials prepared in each embodiment and comparative example was tested according to standard ASTM D2863. The results are shown in Table 1.

[0064] Table 1

[0065] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 31.77 Comparative Example 1 22.43 Example 2 30.41 Comparative Example 2 31.36 Example 3 32.12 Comparative Example 3 30.69

[0066] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the skin-friendly antibacterial foaming material prepared by the present invention has good flame retardant properties.

[0067] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that the carbon-carbon double bond on tetramethyltetravinylcyclotetrasiloxane reacts with the phosphine-hydrogen of the flame retardant 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to generate a flame-retardant cyclosiloxane, and the flame-retardant cyclosiloxane, octamethylcyclotetrasiloxane and maleimide-terminated siloxane react to generate a polysiloxane, and the side chain of the polysiloxane contains a flame-retardant functional monomer, which can give the material excellent flame retardant properties.

[0068] Test Example 2

[0069] Self-healing performance test

[0070] Test method: All examples and comparative examples were made into specimens according to standard GB / 6344-2008, and the tensile strength of the specimens was tested, which was recorded as η 0 ; Cut the sample and overlap the cut surface, heat it at 70℃ for 30min, and test the tensile strength of the sample again, which is recorded as η 1 , the self-repair efficiency W is calculated according to the following formula, W = (η 1 / η 0 )*100%. The results are shown in Table 2.

[0071] Table 2

[0072] Self-repair efficiency (%) Self-repair efficiency (%) Example 1 95.41 Comparative Example 1 94.57 Example 2 94.67 Comparative Example 2 95.24 Example 3 95.11 Comparative Example 3 0

[0073] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the skin-friendly antibacterial foaming material prepared by the present invention has good self-repairing performance.

[0074] By comparison, the self-repairing efficiency of Examples 1 to 3 is greater than that of Comparative Example 3, indicating that the modified polyamide prepared by polymerization of polyetheramine, furan-2,5-dimethyl dicarboxylate, 3,5-diaminobenzenesulfonic acid, and dimethyl malonate and functionalized polysiloxane, modified silica, and chitosan quaternary ammonium salt are blended and foamed to prepare a skin-friendly antibacterial foaming material. The furan group in the modified polyamide main chain can form a dynamic reversible covalent bond with the maleimide groups at both ends of the functionalized polysiloxane, giving the material self-repairing properties.

[0075] Test Example 3

[0076] Antimicrobial performance testing

[0077] Test method: The skin-friendly antibacterial foaming materials prepared in the examples and comparative examples were tested for antibacterial rate by the shaking flask method according to the 2002 edition of the National Technical Specification for Disinfection, and the bacterial species was Staphylococcus aureus. The results are shown in Table 3.

[0078] Table 3

[0079] Antibacterial rate / % Antibacterial rate / % Example 1 95.47 Comparative Example 1 96.04 Example 2 96.21 Comparative Example 2 32.41 Example 3 95.84 Comparative Example 3 95.31

[0080] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the skin-friendly antibacterial foaming material prepared by the present invention has good antibacterial properties.

[0081] By comparison, the antibacterial rates of Examples 1 to 3 are better than that of Comparative Example 2, indicating that the hollow silica is loaded with a foaming agent, the surface of the silica is carboxylated by a silane coupling agent and succinic anhydride modification, and then chitosan quaternary ammonium salt is grafted thereon, giving the material good antibacterial properties.

[0082] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A skin-friendly antibacterial foaming material, characterized in that: The skin-friendly antibacterial foaming material is prepared by blending and foaming a modified polyamide obtained by polymerization of polyetheramine, furan-2,5-dimethyl dicarboxylate, 3,5-diaminobenzenesulfonic acid, and dimethyl malonate, and a functionalized polysiloxane, modified silicon dioxide, and chitosan quaternary ammonium salt; The functionalized polysiloxane is prepared by first reacting tetramethyltetravinylcyclotetrasiloxane with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to obtain a flame-retardant cyclosiloxane, ring-opening polymerization of the flame-retardant cyclosiloxane and octamethylcyclotetrasiloxane, and then capping with a capping agent; the capping agent is prepared by reacting 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane with maleic anhydride; The modified silicon dioxide is prepared by loading a foaming agent on hollow silicon dioxide, then modifying with 3-aminopropyltriethoxysilane to obtain amino silicon dioxide, reacting the amino silicon dioxide with succinic anhydride to obtain carboxylated silicon dioxide, and then grafting chitosan quaternary ammonium salt to obtain the modified silicon dioxide.

2. A method for preparing a skin-friendly antibacterial foaming material, characterized in that: The method comprises the following preparation steps: (1) tetramethyltetravinylcyclotetrasiloxane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and chloroform are mixed in a mass ratio of 1:(0.5-0.7):(20-30), heated to 65-70° C. for reflux reaction for 5-10 min, azobisisobutyronitrile in an amount of 0.01-0.02 times the mass of tetramethyltetravinylcyclotetrasiloxane is added, the reaction is continued for 6-7 h, chloroform is removed by vacuum rotary evaporation, and the mixture is dried at 60° C. for 6-7 h to obtain a flame retardant cyclosiloxane; (2) octamethylcyclotetrasiloxane and flame retardant cyclosiloxane are mixed in a mass ratio of 1:(0.3-0.5), heated to 80° C. under nitrogen protection, mixed for 1 hour, added with a 25wt% tetramethylammonium hydroxide aqueous solution of 0.02%-0.03% by weight of octamethylcyclotetrasiloxane, and then added with a capping agent of 0.3%-0.4% by weight of octamethylcyclotetrasiloxane, and continued to heat to 110-120° C., reacted for 2-3 hours, and continued to heat to 150° C., reduced pressure to 2-2.5 KPa, and reacted for 3-4 hours to obtain a functionalized polysiloxane; (3) under nitrogen protection, polyetheramine and 3,5-diaminobenzenesulfonic acid are mixed at a mass ratio of 1:(0.2-0.3) to obtain a diamine mixture, dimethyl malonate and furan-2,5-dicarboxylate are mixed at a mass ratio of 1:(0.2-0.3) to obtain a diacid methyl ester mixture, and the diamine mixture and the diacid methyl ester mixture are stirred uniformly at a molar ratio of 1:1, wherein the molar ratio refers to the molar ratio of the amino group in the diamine mixture to the methyl ester group in the diacid methyl ester mixture, the stirring speed is 200-300 r / min, the reaction is carried out at 120° C. for 30-40 min, the temperature is raised to 230-240° C., and the reaction is carried out at 300 Pa for 2-2.5 h to obtain a modified polyamide; (4) Mixing supported silica and toluene in a mass ratio of 1:(50-60), uniformly dispersing by ultrasonication at 40 Hz, adding 3-aminopropyltriethoxysilane in an amount of 10-12 times the mass of supported silica, heating to 100-110° C., reflux reaction for 22-24 h, cooling to room temperature, filtering and washing with pure water for 3-4 times, and drying at 60° C. for 6-8 h to obtain amino silica; mixing amino silica, succinic anhydride, 4-dimethylaminopyridine and dichloromethane in a mass ratio of 1:(3-4):(0.7-0.9):(100-150), stirring at room temperature for 10-12 h, filtering and washing with ethanol for 3-4 times, and drying at 60° C. for 6-8 h to obtain carboxylated silica; (5) Carboxylated silica, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and pure water are mixed at a mass ratio of 1:1:(150-160) for 30 minutes, N-hydroxysuccinimide is added in an amount equal to the mass of the carboxylated silica, and stirring is continued for 30 minutes to obtain a silica dispersion, chitosan quaternary ammonium salt and pure water in an amount equal to the mass of the carboxylated silica are added in a mass ratio of 1:(150-160) at 60° C. for 5-6 hours, and then added to the silica dispersion, stirred at 60° C. for 10-12 hours, cooled to room temperature, stirred for 10-12 hours, filtered, and dried at 60° C. for 6-8 hours to obtain modified silica; (6) Grinding the modified polyamide into modified polyamide powder using a ball mill, wherein the diameter of the grinding balls in the ball mill is 6 mm, the grinding time is 10 h, the ball-to-material mass ratio is 1:(1.1-1.2), and the rotation speed of the ball mill is 500-600 r / min; adding the modified polyamide powder into a torque rheometer at 60 r / min and 190 ° C and stirring for 1 min, then adding functionalized polysiloxane, modified silica, and chitosan quaternary ammonium salt and kneading for 6 min, discharging the material and placing it in a foaming mold, placing the foaming mold in a high-temperature foaming machine for foaming, and keeping it at 180 ° C and 11 MPa for 7 min before demolding to obtain a skin-friendly and antibacterial foaming material.

3. The method for preparing a skin-friendly antibacterial foaming material according to claim 2, characterized in that: The preparation method of the end-capping agent in step (2) is as follows: under nitrogen protection, 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and maleic anhydride are weighed in a mass ratio of 1:(2.1-2.2), 1,3-bisaminopropyl-1,1,3,3-tetramethyldisiloxane and toluene are mixed in a mass ratio of 1:(30-40) to obtain solution A, maleic anhydride and toluene are mixed in a mass ratio of 1:(50-60) to obtain solution B, solution B is added dropwise to solution A at a dropping speed of 6 mL / min, reacted at room temperature for 1-1.5 h, then heated to 80° C., acetic anhydride with a mass of 0.7-0.9 times that of maleic anhydride and pyridine with a mass of 0.5-0.7 times that of maleic anhydride are added, the reaction is continued for 3-4 h, and toluene is removed by reduced pressure rotary evaporation to obtain the end-capping agent.

4. The method for preparing a skin-friendly antibacterial foaming material according to claim 2, characterized in that: The preparation method of the supported silica in step (4) is as follows: polystyrene microspheres, hexadecyltrimethylammonium bromide, 25wt% ammonia water and anhydrous ethanol are mixed in a mass ratio of 1:(0.3-0.5):(10-12):(100-150), and after ultrasonication at 40Hz for 50-60min, 5-6 times the mass of tetraethyl orthosilicate of the polystyrene microspheres is added, and the mixture is stirred for reaction for 8-10h at room temperature, filtered and dried at 60°C for 4-6h, and then calcined at 500°C for 6h to obtain hollow silica; the hollow silica is immersed in a foaming agent solution, stirred for 30min, and ultrasonicated at 40Hz for 10-20min, allowed to stand for 24h, filtered, washed with methanol for 3-4 times, and dried at 60°C for 6-8h to obtain supported silica.

5. The method for preparing a skin-friendly antibacterial foaming material according to claim 4, characterized in that: The foaming agent solution is prepared by mixing azodicarbonamide and dimethyl sulfoxide in a mass ratio of 1:(15-17); the particle size of the polystyrene microspheres is 3 μm.

6. The method for preparing a skin-friendly antibacterial foaming material according to claim 2, characterized in that: The amount of the modified polyamide powder, functionalized polysiloxane, modified silicon dioxide and chitosan quaternary ammonium salt in step (6) is: by mass, 100 parts of modified polyamide powder, 1-2 parts of functionalized polysiloxane, 3-5 parts of modified silicon dioxide and 3-5 parts of chitosan quaternary ammonium salt.

7. The method for preparing a skin-friendly antibacterial foaming material according to claim 2, characterized in that: The chitosan quaternary ammonium salt in step (5) and step (6) is hydroxypropyltrimethylammonium chloride chitosan with a substitution degree of 98%.

8. The method for preparing a skin-friendly antibacterial foaming material according to claim 2, characterized in that: The polyetheramine in step (3) is polypropylene glycol bis(2-aminopropyl ether) with a molecular weight of 2000.

9. Use of the skin-friendly antibacterial foaming material prepared by the method for preparing the skin-friendly antibacterial foaming material according to any one of claims 1 to 8 in footwear products.

Citation Information

Patent Citations

  • Thermoplastic elastomer-silicone composition

    CN111601852A

  • Plastic master batch prepared by taking algae as main raw material

    CN112239559A

  • Preparation process of foaming profile with antibacterial function

    CN112795176A

  • Novel block copolymer

    CN114174376A

  • Antibacterial self-repairing polysiloxane elastomer and preparation method thereof

    CN115819775A

Cited By

  • Waterproof thermal insulation material and application thereof

    CN120327067A

  • Antibacterial waterproof material as well as preparation method and application thereof

    CN120776584A